Web-based intelligent e-learning systems technologies and applications - Ma, Zongmin 1965- (Gale virtual reference library, 2006)
"This book offers a complete understanding of the notions, techniques, and methods related to the research and developments of web-based e-learning systems"--Provided by publisher.